Effectiveness of prenatal yoga on pregnant women's anxiety and duration of labour - Diyan Indrayani; Titi Legiati; Chris Sriyanti (PAGEPress Publications, 2023)
The birth process involves physical and psychological mechanisms. Anxiety creates physical and psychological tension, interfering with the birth process. The study aimed to analyze the effectiveness of Yoga on pregnant women's an'iety and labor duration. This study used an experimental design with a Randomized Controlled Trial (RCT) involving 60 pregnant women divided into two groups: Yoga and walking (30 participants each). The variables studied were pregnant women's anxiety and the duration of labor. The sampling technique was conducted using block randomization. Data were analyzed using the Independent T-test. The Yoga group attended 30-minute sessions twice weekly, while the walking group engaged in the same frequency and duration of walking until giving birth. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and one month after the intervention in both groups. The duration of labor was measured using partographs and medical records during delivery for both groups. Data were analyzed using the Shapiro-Wilk test and independent t-test. Pregnant women in both the Yoga and walking groups experienced reduced anxiety scores, with a decrease of 11.6%, and statistically significant p-values of <0.05. The duration of labor was significantly shorter in the Yoga group (mean: 2.65 hours, SD: 1.01) compared to the walking group (mean: 4.01 hours, SD: 2.54), with a mean difference of 1.36 hours and a p-value of <0.05. Prenatal Yoga in the third trimester reduces pregnant women's an'iety and shortens the duration of labor. It can be suggested as an alternative exercise for pregnant women to improve maternal health during pregnancy and childbirth.